2015
DOI: 10.1111/anu.12313
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation ofTenebrio molitormeal as fishmeal substitute for tilapia (Oreochromis niloticus) diet

Abstract: Fishmeal (FM) and soy meal (SM) are the most common protein sources used in fish feed, but they are associated with environmental, economic or production problems. Insects could be an interesting alternative source of protein. This work investigates the nutritive value of Tenebrio molitor meal (TM) and the effect of total replacement of SM by TM (TM/FM diet) or partial replacement of FM by TM (TM/FM/SM diet) versus a diet based in SM and FM (FM/SM diet) for tilapia. We studied the chitin content in TM, the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 56 publications
7
68
2
1
Order By: Relevance
“…Some trials have been conducted in vitro Sánchez-Muros et al, 2015;Yi et al, 2016) but to our knowledge, no trial was performed to evaluate the in vivo digestibility in gilthead seabream. It is very important to observe that, during the entire period of the trial, the TM50 group showed no differences in comparison to TM0 group regarding growth performance even if the crude protein and ether extract apparent digestibility coefficients are lower by -12.0 and -9.6 % than the TM0 group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some trials have been conducted in vitro Sánchez-Muros et al, 2015;Yi et al, 2016) but to our knowledge, no trial was performed to evaluate the in vivo digestibility in gilthead seabream. It is very important to observe that, during the entire period of the trial, the TM50 group showed no differences in comparison to TM0 group regarding growth performance even if the crude protein and ether extract apparent digestibility coefficients are lower by -12.0 and -9.6 % than the TM0 group, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, growth and feeding efficiency were neither affected by inclusion of Tenebrio molitor meal at 250 g/kg in diets for European seabass (Gasco et al, ) nor by inclusion at 500 g/kg in diets for rainbow trout (Belforti et al, ). However, growth was significantly lower when 210 g/kg of T. molitor meal was included in diets for Nile tilapia ( Oreochromis niloticus ; Sánchez‐Muros et al, ). Negative effects of dietary insect meal inclusion on nutrient digestibility, especially on protein digestibility, have been reported, which seems to be related with chitin levels (Belforti et al, ; Kroeckel et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tests conducted with Atlantic salmon showed that replacement of fishmeal with meal of the Black soldier fly is possible without adverse effects on the net growth of the fish, histology, odour, flavour/taste and texture (54) . Other livestock and fish species that have shown positive results by feeding them meal of different insect species such as Black soldier fly, Domesticated house fly, the Oriental latrine fly Chrysomya megacephala (Diptera: Calliphoridae), Yellow mealworm, the Domesticated silkworm Bombyx mori (Lepidoptera: Bombycidae) and the Variegated grasshopper Zonocerus variegatus (Orthoptera: Pyrgomorphidae) are: broiler chickens (56,57) ; tilapia (55,58,59) , African giant snail (Achatina spp.) (60) , African catfish Clarias gariepinus (61)(62)(63)(64)(65)(66)(67) ; and Rainbow trout Oncorhynchus mykiss (68,69) .…”
Section: Insects As Feedmentioning
confidence: 99%